Locus mirabilis et horrendus. Obraz hipermarketu w literaturze polskiej po roku 1989 - Mazurkiewicz, Adam (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
The article deals with the motif of supermarket and its customers in Polish contemporary prose. The image of supermarket is usually created in poetics of grotesque. It's presented as simulacrum. The interested problem evoked by prose is consciousness of customers; it is described by the fact of buying. “I’m doing shopping so I am” can be a new formula of human condition.